Informal social security and its contributions towards meeting the needs of the poor : the case of stokvels in Soweto, Johannesburg - Dube, Nkosiyazi (My University, 2018)
Stokvels have been in existence for many years, and remain an important source of social protection for poor black South Africans. Prior to the democratic dispensation, for many black South Africans, stokvels were a means to save and access credit and, ultimately, served as a mechanism for alleviating poverty. In Post-Apartheid South Africa, social grants have emerged as a mechanism for alleviating poverty. However, not everyone is eligible for the social grants. It is not feasible to achieve a more inclusive social security system; thus, many of the country’s poor people will remain excluded. It is acknowledged though that an informal social security system provides rudimentary social protection. Unfortunately, informal social security has not been considered an important policy area, even though many people depend on it for their protection. Given the importance of informal social security in South Africa, there is a need to investigate the contributions of stokvels in meeting human needs, and how these can be strengthened in order for them to provide adequate social protection. The aim of the study was to explore the contributions of stokvels in meeting the social security needs of their members. The study was qualitative in nature, located within an interpretive paradigm in order to explore and describe the phenomenon. A multiple-case design was adopted for the study. Two different categories of stokvels were studied. The research population consisted of four categories of participants. The first category comprised stokvel members who held positions within the group, or those who were founders of the stokvel; the second category consisted of stokvel members who did not hold any position within the group; the third category comprised those members of a stokvel who had recently experienced an adversity and finally, the fourth category was that of key informant. Snowball sampling was utilised to select three stokvels for the study. A purposive, non-probability sampling technique was used to select three participants who were founders and executive members of their stokvels, 22 participants for the three focus group discussions, one participant who had recently experienced an adversity and the key informant who participated in the study. In-depth, individual, face-to-face interviews, in conjunction with focus group discussions were utilised as methods of data collection. A semi-structured interview schedule was employed as a research tool for the participants who were founding members of their stokvels, for the one who had experienced an adversity, and for the key informant. On the other hand, a focus group guide was used as a research tool for the participants who took part in the focus group discussions. Thematic analysis was employed to analyse data. The main findings that emanated from the study showed that the majority of the participants were of low socio-economic status and relied on their government pensions and informal trading to be able to pay their monthly stokvel contributions. Very few participants were formally employed and had regular income with which to pay their stokvel dues. Also, findings showed that very few participants were property or home owners, and this attests to the fact that most stokvel members are women who are poor and who do not own any property. This was also exacerbated by their low levels of education, as without a formal education, it is difficult for one to find a sustainable job that will bring in regular income. The study also showed that stokvels enabled their members to meet diverse needs. It was revealed that through stokvels, participants were able to address their income insecurity needs, provide for their children’s educational needs, have enhanced access to social capital and also strengthen their livelihoods. The findings also revealed linkages between stokvels and the formal systems, and that these linkages prevent stokvels from being victims of moral hazards, such as misuse of funds by other members. However, some stokvels do not use these linkages to their advantage. It also emerged that for stokvels to be strengthened so that they provide meaningful social protection, there was a need to regulate them and also integrate them with formal institutions; provide them with financial support through subsidies; train members in financial management skills; recognise them as a poverty alleviation strategy; encourage them to collaborate and partner with other stokvels and share best practice knowledge, through diversifying and increasing their membership and also by being flexible and open to new ideas and developments. The study concludes that as much as stokvels are viewed as an informal arrangement, they play an important role in contributing to the social protection needs of the poor, especially for their members and for those who have no formal means of social protection. Stokvels, through their developmental function, have empowered and linked their members to different opportunities and enhanced their livelihoods through the provision of short-term loans to their members. In addition, stokvels are used by the poor not only for financial benefits and risk protection, but it is clear that they are also a vehicle for social cohesion and social networking; thus, they need to be nurtured and supported to provide meaningful social protection. Again, findings from the study show that the provision of subsidies and financial support to stokvels can strengthen their social protection provision. Hence, it is suggested that if the current discourse on ‘radical economic transformation’ is to be implemented, informal arrangements such as stokvels need to be formally recognised, as they are instrumental in social protection provisioning for the poor. Key words: stokvels, social protection, social security, informal social security, formal social security, poverty, Soweto - Johannesburg
A thesis submitted to the Faculty of Humanities in fulfilment of the requirement for the degree Doctor of Philosophy (PhD) in Social Work, University of the Witwatersrand, Johannesburg, 2018
Keywords: Social security; Public welfare